2020
DOI: 10.1371/journal.pone.0228335
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of fertilizing method for different potash sources in cotton (Gossypium hirsutum L.) nutrition under arid climatic conditions

Abstract: Precise choice of potassium (K) source and application method does matter for its costeffectiveness. This study was aimed to evaluate the best source and method of K fertilizer application to improve cotton productivity and profitability under an arid climate. Three different K sources (KNO 3 , K 2 SO 4 and KCl) were applied at 100 kg ha-1 by four methods, i.e. a) basal application, b) side dressing, c) fertigation and d) foliar application of 2% K 2 SO 4. The highest productivity and profitability were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Potassium fertilization diverts the photosynthates to sink tissues [26]. According to the report [27], foliar application of K2SO4 resulted in high seed cotton yield. It has also been reported that, application of naphthalene acetic acid at 30 ppm resulted in more seed cotton yield [28].…”
Section: Fig 2 Influence Of Nutrients and Plant Growth Regulators On ...mentioning
confidence: 99%
“…Potassium fertilization diverts the photosynthates to sink tissues [26]. According to the report [27], foliar application of K2SO4 resulted in high seed cotton yield. It has also been reported that, application of naphthalene acetic acid at 30 ppm resulted in more seed cotton yield [28].…”
Section: Fig 2 Influence Of Nutrients and Plant Growth Regulators On ...mentioning
confidence: 99%
“…Application of thio urea (TU) in corn ( Zea mays L.) (Amin et al, 2013), wheat ( Triticum aestivum L.) (Suryavanshi et al, 2016), potato ( Solanum tuberosum L.) (Mani et al, 2012), and mustard ( Brassica juncea L.) (Pandey et al, 2013) has proved beneficial under stress. Similarly, potassium nitrate (Hussain et al, 2020; Shahzad et al, 2019) and urea (Shalaby, 2018) applications also exhibited potential to induce abiotic stress resilience among field crops. Microbes such as pink pigmented facultative methylobacteria (PPFM) have been shown to affect the release of some sugars and alcohols and improve SCY under moisture stress when combined with cotton stalk biochar/crop residue mulch (Kannan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The PLOS ONE Editors retract this article [ 1 ] because it was identified as one of a series of submissions for which we have concerns about authorship, competing interests, and peer review. We regret that the issues were not addressed prior to the article’s publication.…”
mentioning
confidence: 99%